Evaluation time a practical guide for evaluation - Barrington, Gail Vallance 1945-; Triana-Tremain, Beverly (SAGE Publications, Inc, 2023)
This book is an accessible, contemporary, and comprehensive guide to the concepts and practice of evaluation. Authors Gail Vallance Barrington and Beverly Triana-Tremain integrate new approaches and concerns, and classic frameworks with practical tools that readers can use to design evaluation studies. They show how evaluators measure whether the planned and implemented interventions or services are achieving their goals and objectives, while focusing on the questions most important to the community and organizations in which the evaluation takes place. The book stresses the role of critical and evaluative thinking and self-reflection, and demonstrates the importance of context and equity in today's turbulent environment, offering a new stance for evaluators to support global as well as local issues"--